Continued misuse of multiple testing correction methods in population genetics‐A wake‐up call?. (30th January 2019) - Sethuraman, Arun; Gonzalez, Nicolette M.; Grenier, Christy E.; Kansagra, Khyati S.; Mey, Ken K.; Nunez‐Zavala, Stefany B.; Summerhays, Bryce E. W.; Wulf, Gwendalyn K.
Abstract: Population geneticists often use multiple independent hypothesis tests of Hardy–Weinberg Equilibrium (HWE), Linkage Disequilibrium (LD), and population differentiation, to make broad inferences about their systems of choice. However, correcting for Family‐Wise Error Rates (FWER) that are inflated due to multiple comparisons, is sparingly reported in our current literature. In this issue of Molecular Ecology Resources, perform a meta‐analysis of 215 population genetics studies published between 2011 and 2013 to show (i) scarce use of FWER corrections across all three classes of tests, and (ii) when used, inconsistent application of correction methods with a clear bias towards less‐conservative corrections for tests of population differentiation, than for tests of HWE, and LD. Here we replicate this meta‐analysis using 205 population genetics studies published between 2013 and 2018, to show the same continued disuse, and inconsistencies. We hope that both studies serve as a wake‐up call to population geneticists, reviewers, and editors to be rigorous about consistently correcting for FWER inflation.